Student perception of the cuban trans community in health sciences - Adrian Saborit Rodríguez; Lianne Laura de León Ramírez; Hector Julio Piñera-Castro; Lisandra Aimé Ruiz González; Jonathan Peña Valdivies; Cristian Martínez González (Universidad de Ciencias Médicas de Granma, 2022)
Introduction: in the training of human resources of medical sciences in Cuba, sexual and gender diversity is little addressed. However, this topic has great relevance, especially for health professionals. Objective: to characterize the perception of medical sciences students about the trans community in Cuba. Method: an observational, descriptive and cross-sectional study was carried out in a non-probabilistic sample of 352 subjects, between January and April 2022. The statistical analysis was descriptive. Results: 93,8 % reported knowing the difference between the terms "transsexual" and "transgender"; among them, 86,7 % stated that a difference lies in gender reasignation therapy. Most agreed that they are a socially prejudiced population (94 %), vulnerable (60,2 %), for whom the family and the social environment are important factors (94,9 %). There was majority agreement regarding the fact that there is no discrimination in their health care (72,4 %), as well as the need to include or deepen the approach to these issues in the training of human resources in the health sciences (79,6 %). Conclusions: the participants have basic conceptual notions regarding the trans community in Cuba and identify it as a vulnerable group, a target of social prejudice, with a high affective demand towards the members of their close circle, whose management should be deepened in the formation of human resources of the health sciences in Cuba.